Geographical Differencesin Well-Being of Private B.Ed. College Trainees of Kamrup (Metropolitan) District, Assam - Hemshikha Talukdar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study attempted to examine the differences in well-being among the male and the female Trainees of the Private B.Ed. Colleges in Kamrup (Metropolitan) District of Assam, India with respect to different Geographical Locations. The population size was 676 B.Ed. Trainees including 116 Males and 560 Females. Primary data was collected using Standardized Rating Scale Questionnaire on Well-Being prepared by Dr. (Mrs.) Ripenjeet Kaur.Stratified Random Sampling Method was used taking40 percent sample from each of total male and female B.Ed. Trainee Population, hence 271 Teacher Trainees (191 Males and 80 Females) were taken as the sample size. Statistical analyses were done using Mean, Standard Deviation and Z-tests. Findings revealed no significant difference between the well-beings of Male and Female Trainees of the Private B.Ed. Colleges in Rural Locations. Also, no significant difference was obtained between the well-beings of the Private B.Ed. College Trainees in Urban and Rural Geographical Locations. However, significant difference was found between the well-beings of Male and Female Trainees of the Private B.Ed. Colleges in Urban Locations.